The role of conventional plant breeding in ensuring safe levels of naturally occurring toxins in food crops. (June 2020) - Kaiser, Natalie; Douches, David; Dhingra, Amit; Glenn, Kevin C.; Herzig, Philip Reed; Stowe, Evan C.; Swarup, Shilpa
Abstract: Background: The process of selecting superior performing plants for food, feed and fiber products dates back more than 10, 000 years and has been substantially refined in the last century. While the perceived risks posed by genetically engineered crop plants has been extensively addressed, the extant levels of naturally occurring plant toxins in food crops has received far less attention. Scope and approach: This review discusses how conventional breeding practices are used by plant breeders to develop safe new food crop varieties. Crops are grouped into two categories: 1) crop plants with no significant plant-produced toxins; and 2) crop plants with known plant-produced natural toxins. Examples and crop case studies from each category are used to illustrate the safety considerations of breeding these economically important crops and how plant breeding practices are adjusted prior to commercialization, depending on whether the crop produces known natural toxin(s). Key findings and conclusions: Conventional breeding practices, such as cross- or self-pollinating, shuffle genetic allelic combinations to produce new progeny varieties without giving rise to novel uncharacterized biosynthetic pathways. Therefore, plant breeders can fine tune their practices depending on the crop and specific known natural toxins inherent to that crop species, thereby ensuring a safe food supply for consumers. Breeders often select different varieties of a single food crop for use in disparate markets, each with unique breeding selection practices depending on the desirable characteristics and safety considerations for the portion of the plant that is consumed and the nature of the particular processing industry.